Scanning Tunneling Spectroscopy on Electron-Boson Interactions in Superconductors - Schackert, Michael Peter (Experimental Condensed Matter Physics / Karlsruher Institut für Technologie, Physikalisches Institut, 2014)
This work describes the experimental study of electron-boson interactions in superconductors by means of inelastic electron tunneling spectroscopy performed with a scanning tunneling microscope (STM) at temperatures below 1 K. This new approach allows the direct measurement of the Eliashberg function of conventional superconductors as demonstrated on lead (Pb) and niobium (Nb). Preparative experiments on unconventional iron-pnictides are presented in the end.